G Protein–Coupled Estrogen Receptor 30 Reduces Transverse Aortic Constriction–Induced Myocardial Fibrosis in Aged Female Mice by Inhibiting the ERK1/2 -MMP-9 Signaling Pathway - Wang, Xiaowu; Ma, Jipeng; Zhang, Shuaishuai; Li, Zilin; Hong, Ziwei; Jiang, Liqing; Duan, Weixun; Liu, Jincheng (Frontiers in Pharmacology, 2021)
The incidence of cardiovascular diseases was significantly increased in postmenopausal women. The protection of estrogen on cardiovascular system has been further reported for decades. Although menopausal hormone therapy has been used in many clinical trials, the debatable results indicate that the studies for elucidating the precise molecular mechanism are urgently required. G-protein coupled estrogen receptor 30 (GPR30) is a membrane receptor of estrogen and displays protective roles in diverse cardiovascular diseases. Our present study demonstrated that GPR30 overexpression and its agonist G1 co-administration reduced transverse aortic constriction-induced myocardial fibrosis and preserved cardiac function in aged female mice. MMP-9 expression was markedly increased via ERK1/2 phosphorylation in TAC-injured myocardium of aged female mice. The further results showed that GPR30/G1 activation decreased MMP-9 expression via ERK1/2 inhibition, which further reduced TGF-β1 expression. Inhibition of ERK1/2 signaling pathway by its inhibitor PD98059 suppressed the induction of cardiomyocyte MMP-9 level caused by the GRP30 antagonist G15 and inhibited TGF-β1 expression in cardiac fibroblast in vitro. Thus, the present study may provide the novel drug targets for prevention and treatment of cardiac pathological hypertrophy in postmenopausal women.